The influence of financial distress, board gender diversity, and CEO profile on tax aggressiveness - Yasniar, Maharani; Irawan, Ferry (Educoretax, 2025)
This research is a quantitative study that aims to determine the effect of financial distress, board gender diversity, and CEO profile on tax aggressiveness. This research uses secondary data in the form of financial reports and annual reports of energy sector companies listed on the Indonesia Stock Exchange for the period 2019-2023. A total of 110 observation data was collected from 22 sample companies. Hypothesis testing uses panel data regression analysis with the help of STATA software at a significant level of 5%. The results of tests indicate that (1) financial distress has a negative effect on tax aggressiveness, (2) board gender diversity has a positive effect on tax aggressiveness, (3) CEO education has no effect on tax aggressiveness, and (4) CEO generation has no effect on tax aggressiveness.